Peran Kesehatan dan Gizi Anak terhadap Kemampuan Kognitif Anak Usia Dini - Siti Fatimatuz Zahrah; Selfi Lailiyatul Iftitah (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Children who are malnourished will experience slow development, because the amount of nutritional intake received cannot meet the nutritional needs received by the body, especially the brain, as a result it will interfere with cognitive abilities. So that children will find it difficult to understand learning well, children get tired easily and get sick because of that, children really need good nutrition. The research method uses qualitative methods, which are taken from the phenomena that occur, the type of research uses descriptive analysis, which is directed to describe how the role of children's health and nutrition on the cognitive potential of AUD in RA Perwanida Brawijaya Pamekasan, the source of data in this study is the teacher at RA Perwanida Brawijaya Pamekasan, data collection techniques using observation, interviews and documentation, namely field notes, child development reports, children's photos and children's personal documents as data analysis used. The results showed that: the health condition of the children in RA Perwanida was good, this could be seen when the line activities in the school yard before entering the classroom, when the child was healthy it could be seen from his cheerful, enthusiastic and happy face, the level of his attendance to school and every month holding weight measurements, measuring height and head circumference, the nutritional condition of children at RA Perwanida is good, because the teacher always monitors it by giving vitamin C every day after eating, eating together and giving vitamin A and deworming that has been programmed every day. every month, at RA Perwanida, health and nutrition play an important role in children's cognitive potential, because after implementing health and nutrition, children's cognitive abilities increase.